Highly tunable doping in Ge quantum dots/graphene composite with distinct quantum dot growth evolution. (25th February 2019) - Tong, Ling; Qiu, Feng; Wang, Pan; Huang, Tao; Chen, Anran; Zhou, Xiaohao; Long, Jia; Wang, Rongfei; Yang, Jie; Wang, Chong; Yang, Yu
Abstract: Quantum dots/graphene (QDs/Gr) composites have become the research hotspot recently due to their unique synergistic effect as optical absorption material for next-generation electronic and optoelectronic devices. In this work, Ge QDs/Gr composite is prepared by a simple and effective ion-beam sputtering deposition technique. The intact growth evolution process is detailly investigated by means of the effect of Ge deposition amount, which will induce the enhanced crystallinity in QDs and the reduced defects in graphene. Moreover, a feasible and inspiring strategy to effectively tune doping in graphene by artificial control through changing the deposition amount of Ge atoms on graphene is demonstrated. In addition, charge transfer and interaction strength at the interface of Ge QD and graphene is influenced via the oxygen defect in the QD surface, which is consistent with field-effect transistor test and first-principle calculations. The p-doping characteristics of graphene decorated by Ge QDs may have significant application prospects in energy band engineering of graphene-based building blocks for graphene-based composite development and near-infrared detector applications.